Performance Management Strategy In The Public Works And Spatial Planning Department Of Tanjungpinang City - Saskia Nabila; Delvina Azalia Zalma; Meilita Putri Kheirani; Rangga Renaldi; Satriadi Satriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aimed to analyze the performance management strategies implemented at the Public Works and Spatial Planning Office of Tanjungpinang City. The research type used was descriptive research with a qualitative approach. Data collection techniques were carried out through observation and interviews. The sample used in this study was purposive sampling, with the informants being human resources supervisors at the relevant office. Data analysis was conducted to identify the strategies applied in performance management. The research findings showed that the Public Works and Spatial Planning Office of Tanjungpinang City had implemented several performance management strategies, such as human resource development, measurement and evaluation, reward and sanction provision, and the implementation of information and technology. However, there were several challenges, such as the lack of quality human resources. This study recommended the need for improvements in the performance evaluation system, ongoing training, and better utilization of information technology. These measures were suggested to support the implementation of more effective performance management strategies.